2011
DOI: 10.1590/s1413-78522011000200001
|View full text |Cite
|
Sign up to set email alerts
|

Resultados do tratamento das fraturas do terço proximal do úmero com placas de bloqueio

Abstract: Objective: To analyze the clinical results after proximal humerus fracture fixation using blocked plates and screws. Material and Methods: In the period from November 2003 to January 2008, the authors treated 33 patients with 34 fractures of the proximal humerus. The mean age was 57 years old (33 to 86 years), 14 males and 19 females. All patients were operated in the acute phase, within the first week after the trauma. The patients were treated with open reduction and internal fixation using locking plates. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The internal fixation with LP and screws offers greater stability, favoring early mobility of the affected limb. 4 However, various other methods of osteosynthesis are also capable of providing stability and allowing early mobility. 20 Different osteosynthesis methods provide different degrees of stability, but show similar functional clinical results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The internal fixation with LP and screws offers greater stability, favoring early mobility of the affected limb. 4 However, various other methods of osteosynthesis are also capable of providing stability and allowing early mobility. 20 Different osteosynthesis methods provide different degrees of stability, but show similar functional clinical results.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, different osteosynthesis techniques were used, such as securing sutures, 23 , 24 KW and tension-band, 25 and LP, 4 depending of the material available for each case, which is related to financial cost. However, all patients underwent surgical treatment in accordance with the concepts of minimally invasive osteosynthesis, i.e ., early surgical intervention, minimal soft tissue injury, careful manipulation of the fragments, fracture stabilization, and early rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a review of the literature, we found rates of occurrence of subacromial impact ranging from zero to 10.3% 4 , 6 , 12 , 27 . According to some authors, the plate should be positioned between five and eight millimeters from the apex of the greater tubercle; if not, a mechanical impact on the acromion might occur when the shoulder is raised 9 , 27 , 28 . In our study, we observed five cases of impact caused by placement of the plate in positions that were too high, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly used surgical techniques are: closed reduction and fixation with pins or percutaneous screws, open reduction and internal fixation with plate and screws or with tension band, intramedullary nails, and hemiarthroplasty. 2 , 9 …”
Section: Introductionmentioning
confidence: 99%